The Effect Of Muhasabah On The Academic Achievement Of Professional Medical Program Students - Tenri Sayu Azzahra; Ida Royani; Nur Fadhillah Khalid (Jurnal EduHealth, 2024)
Collage students are academic individual with high levels of intellectual, critical thinking skills, and thoughtful planning in their actions. The quality of students can be observed through the academic achievements they attainment. Various factors can influence the academic performance of medical students, such as self-motivation, family support, campus environment, active participation in organizations, and individual differences in the significance of each factor. One effort to boost the motivation to excel is through a reflection approach, or muhasabah. In the context of medical education, self-reflection helps students become more aware of their personal strengths and weaknesses, allowing them to assess the pros and cons of their learning methods, identify their shortcomings, and find ways to improve, thereby encouraging continuous development of better study skills. This study aims to examine the impact of self-reflection on the academic performance of medical students. The method used is a literature review with a narrative review design to identify and summarize previously published articles on the influence of self-reflection on academic achievement. From the 12 articles reviewed, it was concluded that self-reflection is positive impacts students ' academic performance. Through self-reflection, students can enhance self-discipline and reflective skills in evaluating their learning methods, identifying weaknesses, and seeking improvements, which foster continuous improvement in study skills, ultimately contributing positively to academic performance.